Gender Inequalities in Health and Self-Employment During the Covid-19 Pandemic: Insights From a Southern European City - Lucía Artazcoz; Imma Cortès-Franch; Katherine Pérez; Laia Ollé-Espluga (International Journal of Social Determinants of Health and Health Services, 2026)
This study examines gender differences in self-perceived health and psychological distress among self-employed workers and employees in Barcelona, Spain, during the COVID-19 pandemic. This cross-sectional study used data from the 2021 Barcelona Health Survey. We included a subsample of workers aged 25–64 years (892 men and 885 women). Employment status was classified into four categories: permanent employee, temporary employee, self-employed, or employer. Two health outcomes were analysed: self-perceived health and psychological distress. Gender-stratified analyses were performed. Unlike men, female employers were less likely to belong to higher social classes, less likely to live with a partner, and more likely to have children than other employed women. Self-perceived health did not differ by employment status in either sex; however, psychological distress outcomes diverged: male employers reported better psychological status than male employees, whereas female employers had higher odds of poor psychological status than other employed women. These findings suggest that many female employers may be necessity-driven entrepreneurs, particularly affected by the impacts of the pandemic. Although results for female employers should be interpreted with caution due to the small sample size, they are consistent with a structural interpretation linking gendered care responsibilities, labour market segmentation, and health inequalities.